Competing in foreign markets: a global perspective on national challenges - McDermott, Michael (Henry Stewart Talks, 2009)
International marketing challenges and the national dimension, The domestic environment, Country of origin typology, International marketing challenges: the macro and micro relationship, The world class company, The impact of economic development, Resource-poor undeveloped markets, Resource-rich undeveloped markets, Emerging economies, Developed country economies, Country of origin and impact upon international marketing challenges